Role of AIOU Web TV in Motivating Students to Learn at the Postgraduate Level: A Quantitative Study - Khan, Saliha (PJDOL, 2025)
Web-TV systems are becoming increasingly significant in higher education for the delivery of information services. The two objectives of this quantitative research study were to: determine how students use and are satisfied with Allama Iqbal Open University's (AIOU) Web-TV-based services; and investigate the factors that impact and inspire students to use AIOU Web-TV-based facilities. A self-developed questionnaire with a survey-based structure was utilized to collect information from a sample of 120 AIOU students all over Pakistan, selected systematically from the population of the study. There were 100 valid questionnaires returned in response to the survey with a 83% response rate. Statistical tests were used to analyze the data. The findings showed that students made academic use of the Web-TV-based resources. The majority of students were satisfied with the web-TV services they utilized. The study provides suggestions that the university Web TV administration might utilize to improve AIOU web-TV-based capabilities for students.